The integrated pathway of TGFβ/Snail with TNFα/NFκB may facilitate the tumor-stroma interaction in the EMT process and colorectal cancer prognosis - Hui Li (Nature Portfolio, 2017)
Abstract Substantial evidence has shown that epithelial-mesenchymal transition (EMT) plays critical roles in colorectal cancer (CRC) development and prognosis. To uncover the pivotal regulators that function in the cooperative interactions between cancer cells and their microenvironment and consequently affect the EMT process, we carried out a systematic analysis and evaluated prognosis in CRC specimens. Tumor buds and their surrounding stroma were captured using laser microdissection. We used gene expression profiling, bioinformatics analysis and regulatory network construction for molecular selection. The clinical significance of potential biomarkers was investigated. We identified potential EMT biomarkers, including BGN, MMP1, LGALS1, SERPINB5, and TM4SF4, all of which participated in the integrated pathway of TGFβ/Snail with TNFα/NFκB. We also found that BGN, MMP1, LGALS1, SERPINB5 and TM4SF4 were related to CRC patient prognosis. Patients with higher expression of these individual potential biomarkers had poorer prognosis. Among the identified biomarkers, BGN and TM4SF4 are reported, for the first time, to probably be involved in the EMT process and to predict CRC prognosis. Our results strongly suggest that the integrated pathway of TGFβ/Snail with TNFα/NFκB may be the principal axis that links cancer cells to their microenvironment during the EMT process and results in poor prognosis in CRC patients.